2014
DOI: 10.1186/1471-2407-14-317
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the JAK2/STAT3 pathway in ovarian cancer results in the loss of cancer stem cell-like characteristics and a reduced tumor burden

Abstract: BackgroundCurrent treatment of ovarian cancer patients with chemotherapy leaves behind a residual tumor which results in recurrent ovarian cancer within a short time frame. We have previously demonstrated that a single short-term treatment of ovarian cancer cells with chemotherapy in vitro resulted in a cancer stem cell (CSC)-like enriched residual population which generated significantly greater tumor burden compared to the tumor burden generated by control untreated cells. In this report we looked at the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
137
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 63 publications
12
137
0
Order By: Relevance
“…Several studies evaluated inhibition of JAK2/STAT3 pathway in ovarian cancers, and it is suggested that activation of STAT3 was associated with proliferation, chemo-resistance, and cancer stem-cell phenotype (26)(27)(28)(29)(30). So, it was speculated that worse PFS in the patients with positive p-STAT3 tumors was contributed by a high abundance of the patients that showed chemo-resistance of primary tumors, although significance was not obtained (P= 0.055).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated inhibition of JAK2/STAT3 pathway in ovarian cancers, and it is suggested that activation of STAT3 was associated with proliferation, chemo-resistance, and cancer stem-cell phenotype (26)(27)(28)(29)(30). So, it was speculated that worse PFS in the patients with positive p-STAT3 tumors was contributed by a high abundance of the patients that showed chemo-resistance of primary tumors, although significance was not obtained (P= 0.055).…”
Section: Discussionmentioning
confidence: 99%
“…These are two new and important findings because previous studies have suggested that JAK1 and JAK2 are capable of activating STAT3 in response to inflammatory cytokines in diverse cell culture models (reviewed by Kisseleva et al [20]). Although it was recognized nearly 2 decades ago that JAK1 plays a role in IL-6 signaling (21,45,46), more recent work has singled out JAK2 as the master regulator for STAT3 activation in breast cancer and other malignancies (47)(48)(49). This paradigm is likely the result of the fact that pharmacological agents labeled "JAK2 inhibitors" were being utilized in most of the recently published experiments.…”
Section: Discussionmentioning
confidence: 99%
“…12,18 Recently, STAT3 activation has been implicated in the enrichment of cancer stem cell-like residue population in isolated tumor cells from the ascites of ovarian cancer patients and HEY ovarian cancer cell line after paclitaxel treatment. 19 Of note, persistently activated STAT3 promotes tumor cell proliferation, survival, and invasion via promoting pro-oncogenic pathways including nuclear factor-JB and interleukin-6/GP130/JAK2 signaling and by opposing the STAT1 and nuclear factor-JBYmediated T h 1 antitumor immunity. 20 Collectively, STAT3 exerts global impact on ovarian cancer biology, including drug efflux transporters, prosurvival genes, and immune responses in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%